2008
DOI: 10.1073/pnas.0807813105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene 3′ ends by automated EST cluster analysis

Abstract: The properties and biology of mRNA transcripts can be affected profoundly by the choice of alternative polyadenylation sites, making definition of the 3 ends of transcripts essential for understanding their regulation. Here we show that 22-52% of sequences in commonly used human and murine ''full-length'' transcript databases may not currently end at bona fide polyadenylation sites. To identify probable transcript termini over the entire murine and human genomes, we analyzed the EST databases for positional cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…However, till date a complete set of full-length cDNAs is not available, clustering and DNA mapping studies of human and murine EST databases reveals that of the currently known genes, 15% have no EST-supported 3'end. In other words, the 3'-termini of a significant portion of known genes from these species remains to be identified [22]. Similar results have been obtained by Lopez et al [23].…”
Section: Introductionsupporting
confidence: 55%
“…However, till date a complete set of full-length cDNAs is not available, clustering and DNA mapping studies of human and murine EST databases reveals that of the currently known genes, 15% have no EST-supported 3'end. In other words, the 3'-termini of a significant portion of known genes from these species remains to be identified [22]. Similar results have been obtained by Lopez et al [23].…”
Section: Introductionsupporting
confidence: 55%
“…We observed rare or no occurrence of internal priming events (Table S1 and Extended Experimental Procedures). Thus, the technology is capable of mapping the extensive 3′ end heterogeneity we and others (Iseli et al, 2002; Lopez et al, 2006; Muro et al, 2008) observed in the majority of yeast and human genes in a genome-wide manner and at nucleotide resolution (Figure 1A–D). …”
Section: Resultsmentioning
confidence: 95%
“…Recent estimates indicate that ∼60% of human genes are capable of undergoing alternative polyadenylation (Tian et al. 2005; Muro et al. 2008), which gives rise to mRNAs with 3′‐UTRs of different lengths and often affects transcript stability.…”
Section: Introductionmentioning
confidence: 99%